Four manifestos from 'HCI for Blockchain': A 2018 CHI workshop. (Ubiquity (2045-6271), 2019)
The article offers information on the manifestos of 2018 Conference on Human Factors in Computing Systems in Montréal, Québec to address the emergence of blockchain, and distributed ledger technologies. Topics discussed include understanding the values around blockchain and to embed them into these technologies, engaging with stakeholders and recognize their roles as individuals, organizations or in society as a whole and blockchains should provide trust properties to support program execution.